Sensitivity Pattern of Antimicrobial from Pneumonia Patients in Tertiary Care Hospital - Shahid Ali, Waqas Hussain, Zakia Subhan, Muhammad Ahmad, Mariam Ahmed Mujtaba, Muhammad Usman Ijaz, Muhammad Ishaq Javed, Maira Iqbal, Sudhair Abbas Bangash, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The purpose of this research was to identify the bacterial isolates, the patterns of antibiotic resistance exhibited by those bacteria, as well as the characteristics that are related with individuals who have community-acquired pneumonia. Study Design: Cross-sectional Place and Duration: This study was carried out at Hayatabad Medical Complex from Jan 2022 to April 2022 Methods: Total 83 patients of both gender had pneumonia were presented. Included pneumonia patients were aged between 18-80 years. After obtaining informed written consent, detailed demographic information about the cases that were recruited was recorded. This information included the participants' ages, genders, body mass indexes, educational levels, and marital statuses. Frequency of antimicrobial sensitivity, sensitivity of bacteria and blood culture examination among all cases were assessed. SPSS 22.0 was used to analyze all data. Results: Among 83 patients, majority 51 (61.4%) were males and 32 (38.6%) were females. Mean age of the patients was 61.7±5.37 years and had mean BMI 25.7± 12.29 kg/m2. 63 (75.9%) patients were married and 43 (51.8%) cases were educated. Pulmonary tuberculosis was the most common co-morbidity followed by heart failure, COPD, and HIV/AIDS. Among the most prevalent bacteria isolated were Klebsiella pneumoniae, Acinetobacter sp., and Pseudomonas sp. Ceftriaxone and other third-generation cephalosporins were frequently prescribed to patients with pneumonia. Conclusion: Klebsiella pneumoniae predominated in sputum cultures and showed increased sensitivity to beta-lactam and aminoglycoside classes of antibiotics. Over-60 years, male gender, and tuberculosis infection were the major contributors to increased danger. Keywords: Pneumonia, Bacteria, Antimicrobial Sensitivity, Comorbidities